PENINGKATAN KETERAMPILAN MEMBACA SURAT-SURAT PENDEK MATA PELAJARAN QUR’AN HADITS MELALUI STRATEGI PRACTICE-REHEARSAL PAIRS PADA SISWA KELAS III MI BAITUR ROHIM GEDANGAN SIDOARJO - Rohma, Miftakhul (Journal Of Islamic Elementary School (JIES), 2017)
This research is motivated by the lack of ability to read students' short letters, which is caused by a lack of innovation in using learning strategies. Of the 28 students, only 14 students (50%) have completed while 14 students (50%) have not. To improve reading skills, the researcher used the Practice-Rehearsal Pairs strategy. This strategy aims to ensure that each partner can perform the skill correctly. The purpose of this study was to determine the application of the Practice-Rehearsal Pairs strategy in improving the skills of reading short letters in the third grade Qur'an Hadith subject at MI Baitur Rohim Gedangan Sidoarjo. Then to find out the improvement in reading skills of third grade students of MI Baitur Rohim Gedangan Sidoarjo after using the Practice-Rehearsal Pair strategy. This research method uses a classroom action research method with Kurt Lewin's model. The subjects of this study consisted of 28 third grade students of MI Baitur Rohim Gedangan Sidoarjo. This action uses two cycles. Data collection techniques used are observation, interviews, performance assessment (performance), documentation. The results showed that: The implementation of the Practice-Rehearsal Pairs strategy in the Qur'an Hadith subjects went well through improvements in each cycle. This is because the student activity in the first cycle has not been reached 76.34 (enough), although the teacher activity in the first cycle has been achieved with a score of 81.45 (good). In cycle II, the result of student activity increased to 90.32 (very good) and the result of teacher activity increased to 89.84 (very good). 2) Improved reading skills of short letters through the Practice-Rehearsal Pairs strategy can improve students' reading skills. In the first cycle the class average was 73.89 good (B) and the second cycle was 90.04 very good (SB). The increase in the percentage of student learning completeness in the first cycle was 68% (medium) and in the second cycle it increased to 89% (high).